1999
DOI: 10.1136/thx.54.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Relation of the perception of airway obstruction to the severity of asthma

Abstract: Background-Patients with a poor perception of their symptoms of asthma seem to have an increased risk of an asthma attack. The influence of factors such as airway calibre, bronchial hyperresponsiveness, age and sex on the "perceptiveness" of a patient are poorly understood. It is of clinical importance to identify patients who are likely to have a poor perception of their symptoms. We have studied the perception of bronchoconstriction by asthmatic patients during a histamine provocation test and analysed the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
2
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 21 publications
(13 reference statements)
7
87
2
3
Order By: Relevance
“…Apter et al (1) reported that patients with lower forced expiratory flow between 25% and 75% of the vital capacity (FEF ) tended to be less accurate perceivers. Chetta et al (24) found that poor perception was associated with asthma severity and Bijl-Hofland et al (25) reported that low baseline forced expiratory volume in 1 s (FEV 1 ) and high hyperresponsiveness were associated with a low perceptiveness of bronchoconstriction. In contrast, Pfeiffer et al (14) concluded that good and poor perceivers did not differ in terms of the severity or duration of asthma and Fritz et al (11) reported that children s perceptual accuracy of symptoms was not related to severity.…”
Section: Discussionmentioning
confidence: 99%
“…Apter et al (1) reported that patients with lower forced expiratory flow between 25% and 75% of the vital capacity (FEF ) tended to be less accurate perceivers. Chetta et al (24) found that poor perception was associated with asthma severity and Bijl-Hofland et al (25) reported that low baseline forced expiratory volume in 1 s (FEV 1 ) and high hyperresponsiveness were associated with a low perceptiveness of bronchoconstriction. In contrast, Pfeiffer et al (14) concluded that good and poor perceivers did not differ in terms of the severity or duration of asthma and Fritz et al (11) reported that children s perceptual accuracy of symptoms was not related to severity.…”
Section: Discussionmentioning
confidence: 99%
“…(11)(12)(13) Others, however, have found no such association. (3) However, 21 (39.5%) did not perceive any changes in the degree of dyspnea even after a 20% fall in FEV 1 (Figure 3). …”
Section: Discussionmentioning
confidence: 99%
“…However, when the patients were stratified by FEV 1 , the authors observed, by means of multiple regression analysis, that low baseline FEV 1 was associated with poorer perception of dyspnea. (3) Another…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations